Application of Benson Therapy in Nursing Care of Femur Fracture Patients with Acute Pain - Sekar Pramudya Wardani; Idrawati Bahar; Yessi Fadriyanti (Jurnal Kesehatan Cendikia Jenius, 2024)
A fracture is a break in the continuity of a bone, a crack or break in an intact bone, which is usually caused by trauma/force or physical force. The main priority nursing problem that arises in femur fractures is acute pain. Pain is the body's way of telling us that something is wrong. . Based on data from RSUP Dr. M.Djamil Padang, during the last 3 months, namely February – April 2024, the number of femur fracture cases was 62 cases. The aim of this study was to determine the effect of applying Benson Relaxation Therapy on reducing pain in femur fracture patients. This research uses a descriptive observational research design in the form of a case report. The population in this study was 13 people with femur fractures. The number of research samples was 2 people with a sampling technique, namely accidental sampling, where any patient who happened to meet the researcher could be used as a sample. The journal analysis used in this research is the PICO method. Based on the results of the evaluation carried out by the author on patient 1, it shows that the pain decreased from a pain scale of 5 to a pain scale of 3 and in patient 2 there was also a decrease in pain from a scale of 4 down to a scale of 3. It was concluded that the intervention given to the patient showed that there was The influence of Benson Relaxation Therapy on efforts to reduce pain in Femur Fracture patients in the Irna Surgical Trauma Center at RSUP Dr. M. Djamil Padang. Benson Relaxation Therapy is expected to be an alternative in nursing care to reduce pain in fracture patients at RSUP Dr. M. Djamil Padang.